Recent advances of exosomes in immune modulation and autoimmune diseases - Tan, Lina; Wu, Haijing; Liu, Ying; Zhao, Ming; Li, Duo; Lu, Qianjin (Autoimmunity (Chur, Switzerland), 2016)
Exosomes are small membrane-bound vesicles (30-100 nm) that are secreted by different types of cells and they have been well documented to resemble saucers or flattened spheres under the electron microscope. Recently, evidence indicates that exosomes play important roles in the immune modulation and are associated with the immune pathogenesis of autoimmune diseases, including rheumatoid arthritis (RA), Sjogren's syndrome (SS) and systemic lupus erythematosus (SLE). In this review, we will summarize current research advances of exosomes in immunoregulation, pathogenesis, diagnosis and therapeutics of autoimmune diseases.